Keputusan Hukum Pembolehan Mengemudi bagi Perempuan Saudi Arabia Ditinjau dalam Perspektif Maqashid As-syari’ah - Ramadhan, Reza Bakhtiar; Shofwan, Irham (Journal of Islamic World and Politics, 2019)
This article examines Saudi's latest fatwa regarding the possibility of Saudi women driving in the perspective of maqashid asy-syaria'ah. The description will be focused on the preliminary law on the prohibition of Saudi women driving until the emergence of the law allowing women to drive. In the process, this law change has occurred dialectics between Umara’ (kingdom), Ulama (fatwa institution) and Ummah. Not only stop there, this fact shows that Umara’ (kingdom) in this case has authority over on fatwa institution. It is known for us that Saudi women have limited space in public space. Many Saudi law decisions are considered to be detrimental to women, but then the presence of this new fatwa becomes a breeze for Saudi women. But it should be noted that the emergence of legal fatwa of the Saudi woman driving this still refers to the maqashid as-syariah which aims to benefit humanity, especially Saudi women in one side, and nation stability in the other.